Answer:
(-5, 101) or (1, -7)
Explanation:
The gradient of a function is zero when its first differential is zero
Taking first derivative of y = x³ + 6x² - 15x + 1
we get
![(dy)/(dx) = (d)/(dx)(x^3+6x^2-15x\:+\:1)](https://img.qammunity.org/2023/formulas/mathematics/college/kcmpagoqtfmt52tubwo75x4r1293kdo8gt.png)
![= (d)/(dx)(x^3)+ (d)/(dx)(6x^2) - (d)/(dx)(15x)\:+\: (d)/(dx)(1)\\\\](https://img.qammunity.org/2023/formulas/mathematics/college/p2iqhqo236m1dvlm9cl5iezdoc8wk74tzr.png)
![= 3x^2 + 2(6x) - 15 + 0\\\\\\= 3x^2 + 12x - 15x\\](https://img.qammunity.org/2023/formulas/mathematics/college/x3a1mnmf1tv9k7oc7fg2ablgwitpct6ab7.png)
Set this first differential to 0, find the solution set for x
![3x^2 + 12x - 15x =0](https://img.qammunity.org/2023/formulas/mathematics/college/xrzs0efwsjvi4i8g35no5s40zj3r7f2xb9.png)
This is a quadratic equation which will have 2 solutions for x.
First divide throughout by 3
![= > x^2 + 4x - 5 = 0](https://img.qammunity.org/2023/formulas/mathematics/college/gxol3d03z2ulowg9a45mdu7vyzcd6gbs7h.png)
Factor the term:
![= > x^2 + 4x - 5 = 0\\\\== > (x -1)(x + 5) = 0\\== > x - 1 =0 \text { or } x + 5 =0\\\\](https://img.qammunity.org/2023/formulas/mathematics/college/efe5ulalln7qtzqa8yeqykkc7jd2vumuq7.png)
This means x = 1 or x = -5 is the solution set
To find the y value corresponding to these values of x, plug in each of these x values in the original equation and solve for y
Plug in x = 1 into equation x³ + 6x² - 15x + 1
=> 1³ + 6(1)² - 15(1) + 1
=> 1 + 6 - 15 + 1
=> -7
So one point is (1, -7)
Looking at the choices we can eliminate the first and last choices
Looking at choices 2 and 3 we see that only one of them has x = -5 which is the other solution value. This is the second choice
So the correct answer is second choice
(-5, 101) or (1, -7)
Note we did not have to go through the pain of computing y for x = -5